INTERSECTION OF HEALTH, GENDER AND CULTURE IN DOMESTIC SPACE: A CRITICAL PERSPECTIVE ON REFERENCES TO HEALTH ISSUES IN SELECT KANNADA TEXTS - Dr. Renuka L. Nayak, (IJRDO - Journal of Social Science and Humanities Research, 2025)
In the present society, health care system has improved and is able to reach the corners of the villages in India. But still women’s health is compromised on the name of fulfilling familial roles and responsibilities. The present  article attempts to highlight the critical understanding of the conditions of the marginalised Muslim community women represented by Sara Aboobacker and Banu Mushtaq in select Kannada fiction. The close reading of the literary texts with health humanities perspective provides ample narratives highlighting the interplay between gender and power dynamics in the domestic space. The article would be valuable as it traces link between gender, lack of nutrition, reproductive health of the women, and mental and physical illnesses caused due to denial, negligence and ignorance.